India : Report on the Observance of Standards and Codes (ROSC)-Data Module. (IMF Staff Country Reports; Country Report, 2004)
A summary of India's dissemination practices relative to the special data dissemination standard (SDDS) is provided. This report is based on the information provided by Indian authorities and data users prior to and during a staff mission from May 13-30, 2002, as well as publicly available information. The assessment of India's data dissemination practices against the SDDS is also provided. A summary assessment of the quality of the principal macroeconomic datasets is also discussed. Finally, the report sets out recommendations to achieve further improvements in India's statistics.